1996
DOI: 10.1111/j.1540-8167.1996.tb00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sustained Load on Dispersion of Ventricular Repolarization and Conduction Time in the Isolated Intact Rabbit Heart

Abstract: Sustained load shortens the ERP and the mean APD90, and at the same time increases dispersion of APD90 and prolongs activation times. These findings provide additional insight into the arrhythmogenic mechanisms of sustained mechanical load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 37 publications
(1 reference statement)
3
41
1
2
Order By: Relevance
“…Previous studies on refractoriness resting membrane potential between successive activations. This is supported by the demonstration of a close correlaSeveral studies using isolated hearts under isovolumetric tion between VF interval and effective refractory period [8,9,12,19,20] or ejecting [10,21,22] conditions have [15]. However, Janse et al [28] have recently challenged shown a significant (7-22%) shortening in monophasic the multiple wavelet assumption, based on the observation action potential duration and refractory period during a that several single wandering spiral waves and two insustained increase in left ventricular volume, consistent dependent wandering reentrant wavefronts, in addition to with our findings, although Calkins [23,24] reported only multiple wavelets, may give rise to similar epicardial minor (,2%) changes in these parameters in blood-perelectrograms.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Previous studies on refractoriness resting membrane potential between successive activations. This is supported by the demonstration of a close correlaSeveral studies using isolated hearts under isovolumetric tion between VF interval and effective refractory period [8,9,12,19,20] or ejecting [10,21,22] conditions have [15]. However, Janse et al [28] have recently challenged shown a significant (7-22%) shortening in monophasic the multiple wavelet assumption, based on the observation action potential duration and refractory period during a that several single wandering spiral waves and two insustained increase in left ventricular volume, consistent dependent wandering reentrant wavefronts, in addition to with our findings, although Calkins [23,24] reported only multiple wavelets, may give rise to similar epicardial minor (,2%) changes in these parameters in blood-perelectrograms.…”
Section: Discussionmentioning
confidence: 69%
“…Numerous factors predispose to arrhythof conduction velocity and refractory period [11]. mias, including increased sympathetic tone, ionic disturChanges in refractoriness due to stretch vary in magbances, ischaemia and structural abnormalities associated nitude in different regions of the left ventricle [12], and with infarction and fibrosis [3]. However, alterations in between left and right ventricles [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Franz et al 3 have reported that myocardial stretch induces ventricular arrhythmias triggered by early afterdepolarizations (EADs). Also, they showed that sustained load increases the dispersion of ventricular repolarization, suggesting reentry as an another mechanism of stretch-induced arrhythmias, 5 although development of the arrhythmias was not quantified.…”
Section: Echano-electrical Feedback Phenomenon (Mef)mentioning
confidence: 99%
“…These studies suggest that stretch-induced arrhythmias occur due to depolarization-induced automaticity and/or triggered activity. Also, Franz et al 5 have shown that sustained load increases the dispersion of epicardial ventricular repolarization, and suggested reentry as another mechanism of stretch-induced arrhythmias. The present results suggest that acute pressure overloading of the LV increases the spatial dispersion of epicardial and endocardial MAP durations and may cause reentrant arrhythmias because arrhythmias developed in association with the increased difference in MAP durations and were suppressed by Gd 3+ in accordance with elimination of the increase in the difference.…”
Section: Mechanisms Of Stretch-induced Arrhythmiasmentioning
confidence: 99%
“…27,32 Mechanical stretch can facilitate arrhythmias by depolarisation of the membrane potential, premature depolarisations and dispersion in refractoriness. 33,34 Furthermore, the increase in heart rate during pregnancy may act as a trigger in susceptible patients. 35 There are also indications that oestrogen and progesterone may contribute to altered cardiac repolarisation facilitating arrhythmias.…”
Section: Haemodynamic Alterations During Pregnancymentioning
confidence: 99%